A survey of the praying mantises of Rwanda, including new records (Insecta, Mantodea) - Tedrow, Riley; Nathan, Kabanguka; Richard, Nasasira; Svenson, Gavin J. (Zootaxa, 2015)
We report the results of two surveys targeting praying mantises in four localities in Rwanda, specifically Akagera National Park, Nyungwe National Park, Volcanoes National Park, and the Arboretum de Ruhande at the National University of Rwanda. Using an assortment of collecting techniques, including metal halide light traps, sweep netting vegetation and general searching, we obtained 387 adult and 352 juvenile specimens, representing 41 species. A total of 28 novel species records for Rwanda are added to the 18 previously recorded species for the country, in addition to 20 novel species records for the broader region, including neighbouring Uganda and Burundi. This study provides high resolution images of the dorsal habitus of both sexes of representative species, both pinned and living. Species distribution records are presented and discussed. With a 155% increase in species recorded from Rwanda, this survey illustrates the need for further taxonomic work in the region.